2017
DOI: 10.1111/mec.14015
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐biased transcriptome divergence along a latitudinal gradient

Abstract: Sex-dependent gene expression is likely an important genomic mechanism that allows sex-specific adaptation to environmental changes. Among Drosophila species, sex-biased genes display remarkably consistent evolutionary patterns; male-biased genes evolve faster than unbiased genes in both coding sequence and expression level, suggesting sex differences in selection through time. However, comparatively little is known of the evolutionary process shaping sex-biased expression within species. Latitudinal clines of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 137 publications
(291 reference statements)
7
40
0
Order By: Relevance
“…In a previous experiment, I found that many more male-biased than female-biased genes diverged genetically among eight D. serrata populations (Chapter 3) (Allen et al 2017a). A similar result has also been observed among two D. melanogaster populations (Hutter et al 2008;Muller et al 2011;Huylmans and Parsch 2014).…”
Section: Introductionsupporting
confidence: 60%
See 4 more Smart Citations
“…In a previous experiment, I found that many more male-biased than female-biased genes diverged genetically among eight D. serrata populations (Chapter 3) (Allen et al 2017a). A similar result has also been observed among two D. melanogaster populations (Hutter et al 2008;Muller et al 2011;Huylmans and Parsch 2014).…”
Section: Introductionsupporting
confidence: 60%
“…Third, as previously described (Chapter 3) (Allen et al 2017a), sexspecific gene expression of eight wild populations was measured to assess potential constraints to population-specific divergence in SBGE.…”
Section: Biological Samples Rna Extraction and Microarray Hybridisationmentioning
confidence: 99%
See 3 more Smart Citations